KONTRIBUSI PAJAK DAN RETRIBUSI DAERAH UNTUK KOTA PAGAR ALAM - Ryan Al Rachmat (Jurnal RATRI (Riset Akuntansi Tridinanti), 2022)
The purpose of this study is to find out how much the Local Taxes and Retribustion and their contribution to the Original Local Government Revenue of Pagar Alam City for the 2014-2019 period. The data used is secondary data obtained from the Central Statistics Agency of Pagar Alam City. Quantitative data analysis was carried out using the Contribution Ratio. The results of the analysis show that Local Tax revenues have increased from 2014 to 2018 and have decreased in 2019. On the other hand, Local Retribution revenues show an increasing trend every year. Based on the overall contribution ratio, the level of local tax contribution to Original Local Government Revenue is at a percentage of 10% -20% with less criteria. The smallest percentage was shown in 2015 at 10.38% and the highest in 2019 was 15.10%. Meanwhile, the level of Local Retribution Contribution is at a percentage of 0-10% which is classified as Very Less. The percentage shows below 6%, namely in 2018 it was 3.45% and the highest percentage was in 2014 which was 5.86%. Based on these results, it can be concluded that the contribution of local taxes and retribution to Original Local Government Revenue is still not optimal, so that strategic steps are needed from the local government to be able to maximize regional tax and retribution revenue.Keywords: Contribution, Original Local Government Revenue, Local Taxes and Retribution